2016
DOI: 10.1097/j.pain.0000000000000602
|View full text |Cite
|
Sign up to set email alerts
|

Patient phenotyping in clinical trials of chronic pain treatments: IMMPACT recommendations

Abstract: There is tremendous inter-patient variability in the response to analgesic therapy (even for efficacious treatments), which can be the source of great frustration in clinical practice. This has led to calls for “precision medicine”, or personalized pain therapeutics (i.e., empirically-based algorithms that determine the optimal treatments, or treatment combinations, for individual patients) that would presumably improve both the clinical care of patients with pain, and the success rates for putative analgesic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
282
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(290 citation statements)
references
References 273 publications
(373 reference statements)
5
282
0
3
Order By: Relevance
“…This is the only trial in which a pre-specified primary analysis demonstrated a difference in treatment versus placebo response in patient subgroups identified by phenotyping. These results are very promising, but require replication as well as use of phenotyping measures that would be suitable for larger confirmatory trials and use in clinical practice 188 . Phenotyping could also be used to test whether certain patients have a more robust response to non-pharmacological treatments, for example, invasive, psychological and complementary interventions 188 , as well as to identify which patients are most likely to respond to combinations of treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the only trial in which a pre-specified primary analysis demonstrated a difference in treatment versus placebo response in patient subgroups identified by phenotyping. These results are very promising, but require replication as well as use of phenotyping measures that would be suitable for larger confirmatory trials and use in clinical practice 188 . Phenotyping could also be used to test whether certain patients have a more robust response to non-pharmacological treatments, for example, invasive, psychological and complementary interventions 188 , as well as to identify which patients are most likely to respond to combinations of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…These results are very promising, but require replication as well as use of phenotyping measures that would be suitable for larger confirmatory trials and use in clinical practice 188 . Phenotyping could also be used to test whether certain patients have a more robust response to non-pharmacological treatments, for example, invasive, psychological and complementary interventions 188 , as well as to identify which patients are most likely to respond to combinations of treatments. Indeed, given the importance of expectations and psychological and social factors — including adaptive coping and catastrophizing — in the development and maintenance of chronic neuropathic pain, it would not be surprising if phenotyping has a great part to play in demonstrating the efficacy of psychological interventions as it does for medications.…”
Section: Discussionmentioning
confidence: 99%
“…Individualized treatment requires methods to reliably compare individual perceptions of painful stimuli and individual responses to analgesia in the ED 12. Measurement of pain and response to pain treatment is difficult because of the chaotic ED setting.…”
Section: Introductionmentioning
confidence: 99%
“…[175] Similarly, in clinical analgesic trials for chronic pain, detailed phenotyping of patients may provide information related to factors that predict not only the risk of persistent pain, but also the response to treatment. [55] This is particularly relevant given emerging data that mechanisms and efficacy of potential interventions for neuropathic pain differ between males and females. [124] Core phenotyping domains recommended as part of the Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (IMMPACT) include: pain qualities; psychosocial measures; sleep; and quantitative sensory testing, including conditioned pain modulation.…”
Section: Introductionmentioning
confidence: 99%
“…[124] Core phenotyping domains recommended as part of the Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (IMMPACT) include: pain qualities; psychosocial measures; sleep; and quantitative sensory testing, including conditioned pain modulation. [55] However, as evidence increases for long-term effects following pain and stress in early life, should early life experience also form part of a comprehensive pain history and patient phenotyping?…”
Section: Introductionmentioning
confidence: 99%